The Effect of the Art-themed Activities on Mathematics Achievement and Student Views - Berna Yıldızhan; Ozlem Cezikturk (Indonesian Research Journal in Education |IRJE|, 2022)
This study was aimed to examine the effect of teaching with art-themed activities on students' mathematics achievement and to examine students' attitudes on the teaching process. The research was carried out with a total of 52 fifth grade students studying in Istanbul (Turkey). The research has a hybrid design in which qualitative data are used to support quantitative data. In the study carried out with the quasi-experimental research method, the experimental group was taught with art-themed mathematics activities, while the control group was taught with the activities in the Ministry of Education textbook. As a result of research, it was found that teaching mathematics with art-themed activities was more effective in increasing math achievement than teaching with the Ministry of Education textbook. Students considered teaching as fun in general through art-themed activities and expressed that they learned better by having fun. Findings are discussed with a reference to relevant and recent literature.